Autoantibodies against β1‐Adrenergic Receptors: Response to Cardiac Resynchronization Therapy and Renal Function. Issue 1 (26th October 2015) - MICHELUCCI, ANTONIO; D'ELIOS, MARIO MILCO; STICCHI, ELENA; PIERAGNOLI, PAOLO; RICCIARDI, GIUSEPPE; FATINI, CINZIA; BENAGIANO, MARISA; NICCOLAI, ELENA; GRASSI, ALESSIA; ATTANÀ, PAOLA; NESTI, MARTINA; GRIFONI, GINO; et al.
Abstract : Background: Cardiac resynchronization therapy (CRT) nonresponse remains a major clinical problem. Autoantibodies specific for the β1‐adrenergic (β1‐AAbs) and muscarinic (M2‐AAbs) receptors are found in patients with chronic heart failure (HF) of various etiologies. Materials and Methods: We retrospectively analyzed 73 HF patients (median age 67 years, 84% males, New York Heart Association II–IV, in sinus rhythm, left ventricular ejection fraction <35%) who received CRT defibrillator (CRT‐D) from 2010 to 2013. β1‐AAbs and M2‐AAbs were measured by enzyme‐linked immunosorbent assay. Echocardiography was used to assess CRT response (reduction >15% in left ventricular end‐systolic volume at 6 months follow‐up). Renal function (RF) parameters (creatinine [Cr], blood urea nitrogen [BUN], estimated glomerular filtration rate [eGFR Modified Diet in Renal Disease], cystatin C [Cys‐C], and neutrophil gelatinase‐associated lipocalin [NGAL]) were also evaluated. Results: A significantly higher percentage of patients positive for β1‐AAbs (OD sample/OD reference ratio >2.1) in nonresponders than in responder patients was observed (57% vs 27%, P = 0.004). No influence of M2‐AAbs on CRT‐D response was demonstrated. β1‐AAbs were predictive of a poor CRT‐D response (odds ratio [OR] [95% confidence interval (CI)] 3.64 [1.49–8.88], P = 0.005), also after adjustment for RF parameters (OR [95% CI] 4.95 [1.51–16.26], P = 0.008) observed to influence CRT‐D response (Cr P = 0.03, BUN P = 0.009, Cys‐C P = 0.02). The positive rates of β1‐AABs in patients with abnormal blood level of Cr, eGFR, Cys‐C, and NGAL were significantly higher than those with normal levels (P = 0.03, P = 0.02, P = 0.001, P = 0.007, respectively). Conclusions: Our study suggests that (1) the evaluation of β1‐AAb is useful to identify responders to CRT‐D; (2) the presence of β1‐AAbs is in relationship with elevated renal function parameters.